Analysis of Exhaust Emission of Vehicles in Dhaka City of Bangladesh (Global Journal of Science Frontier Research, 2013)
Mega cities in South Asia are an epitome of traffic snarls and resulting vehicular pollution. Dhaka, a center of polity and economy in Bangladesh, is no exception. This study is focused on the measurement of air pollution levels at traffic congestion and road in Dhaka City. The aim of this paper is to discuss the vehicle engine emissions and the technologies and methodologies available to help reduce these emissions. It has been revealed that the pollution level at traffic congestions has considerably improved due to the large scale introduction of CNG vehicles in Dhaka city. Vehicle exhaust emission level assessment data show that Dhaka city is exposed to high concentration of CO, NO x and SO x . Some recommendations for air pollution control in Dhaka city are also incorporated in the paper.
Keywords: exhaust emissions; vehicle emission standards; air quality standards; flue gas analyzer